Microstructure and tribological properties of aluminum matrix composites reinforced with ZnO-hBN nanocomposite particles - Macit, Cevher Kuersat; Albayrak, Muhammet Gokhan; Tanyeri, Burak; Gurgenc, Turan; Ozel, Cihan (Walter de Gruyter Gmbh, 2024)
In this study, pure and hBN-doped ZnO nanoparticles were synthesized by sol-gel method. ZnO-hBN nanoparticles were mixed with pure aluminum powders and samples were prepared using powder metallurgy processing parameters. It was observed that Al, ZnO, and hBN nanocomposite particles formed homogeneously. With the addition of ZnO-hBN, significant changes occurred in hardness, wear, and friction coefficient values compared to pure Al samples. The highest hardness value in the samples is mesh. It was obtained as 105 HB in 10 wt.% hBN added sample. In the wear tests, it is seen that the wear resistance is seven times higher in the 1 wt.% hBN added sample compared to the pure Al sample, while the friction coefficient decreases with the increase of the hBN additive.
Keywords: hexagonal boron nitride; zinc oxide; aluminum matrix composite; powder metallurgy; tribology